2022
DOI: 10.1002/adfm.202112399
|View full text |Cite
|
Sign up to set email alerts
|

Critical Roles of Mechanical Properties of Solid Electrolyte Interphase for Potassium Metal Anodes

Abstract: The mechanical properties of the solid electrolyte interphase (SEI) have attracted increasing attention, but their importance in guiding electrolyte design remains ambiguous. Here it is revealed that, despite a decrease in ionic conductivity for both electrolyte and SEI, exceptional cycling performance of K-metal batteries is achieved in a low concentration carbonate electrolyte by optimizing the mechanical stability of the SEI. The SEI formed in the studied carbonate electrolytes is predominantly organic. Its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 77 publications
(41 reference statements)
0
22
0
Order By: Relevance
“…Despite the appealing features of PMBs, their development has been impeded by a multi tude of obstacles at the anode side thus far, including unstable solid electrolyte interphase (SEI), large volume expansion and uncontrollable growth of K dendrites. [15][16][17][18] To address these challenges, strategic solutions have recently been proposed: (i) modifying the electrolyte to enable a durable SEI layer on the surface of K metal, which is expected to initiate with reversible plating/stripping process; [19][20][21] (ii) engineering the interface between K anode and electrolyte via the creation of artificial coating to inhibit the generation of dendrites; [22][23][24][25][26] (iii) strengthening the interaction between current collector and K anode to homogenize the local current and mitigate the dendritic growth. [27][28][29] To date, the current collectors employed for the anode of alkali metal batteries mainly encompass two types: 3D free-standing supports and commercial Al/Cu foils.…”
Section: Doi: 101002/adma202202685mentioning
confidence: 99%
“…Despite the appealing features of PMBs, their development has been impeded by a multi tude of obstacles at the anode side thus far, including unstable solid electrolyte interphase (SEI), large volume expansion and uncontrollable growth of K dendrites. [15][16][17][18] To address these challenges, strategic solutions have recently been proposed: (i) modifying the electrolyte to enable a durable SEI layer on the surface of K metal, which is expected to initiate with reversible plating/stripping process; [19][20][21] (ii) engineering the interface between K anode and electrolyte via the creation of artificial coating to inhibit the generation of dendrites; [22][23][24][25][26] (iii) strengthening the interaction between current collector and K anode to homogenize the local current and mitigate the dendritic growth. [27][28][29] To date, the current collectors employed for the anode of alkali metal batteries mainly encompass two types: 3D free-standing supports and commercial Al/Cu foils.…”
Section: Doi: 101002/adma202202685mentioning
confidence: 99%
“…This inorganic-rich SEI is generally believed to facilitate the interfacial ion diffusion 30 and provide sufficient mechanical strength to accommodate volume change of "hostless" K. 31 Meanwhile, the diluent cosolvent is thought to be beneficial to the formation of a homogeneous SEI, 27 which renders good mechanical stability for accommodating deformation. 32 Please do not adjust margins Please do not adjust margins stage (Fig. 4e, f).…”
Section: Resultsmentioning
confidence: 99%
“…A desirable SEI should have the robust mechanical strength and good elastic/plastic properties, so that it cannot only endure the stress/strain change of the anodes during charging and discharging, but also to some extent have a shear modulus to stop the dendrite growth [278]. As shown in figure 19(b), a recent study showed that despite a decrease in ionic conductivity for both electrolyte and SEI, exceptional cycling performance of K-metal batteries is achieved in a low concentration carbonate electrolyte by optimizing the mechanical stability of the SEI [279]. The inorganic content in SEI increases with increasing electrolyte concentration and corresponds to an increase in Young's modulus (E) and ionic conductivity of SEI and a decrease in elastic strain limit (ε Y ).…”
Section: Mechanical Propertiesmentioning
confidence: 99%